2019
DOI: 10.2147/hiv.s229285
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence And Associated Factors Of Enacted, Internalized And Anticipated Stigma Among People Living With HIV In South Africa: Results Of The First National Survey</p>

Abstract: BackgroundThis paper reports on the first national implementation of the “People Living with HIV (PLHIV) Stigma Index” in South Africa. The aim of this study was to investigate the prevalence and correlates of HIV-related stigma in a large sample of PLHIV in South Africa.MethodsThis cross-sectional survey interviewed 10,473 PLHIV 15 years and older with the PLHIV Stigma Index in two districts per province (N=9) in South Africa in 2014.ResultsThe two most common enacted HIV-related stigma items were “being goss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
4
17
2
Order By: Relevance
“…They were concerned about possible breaches of confidentiality as well as discrimination. While this is in line with previous research from the UK [ 19 ], US [ 6 ], and from South Africa [ 34 ], our study has shown that many PLWH still experience enacted or anticipated stigma in the form of institutional or social dishonour. Although our study found that ‘courtesy’ stigma (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…They were concerned about possible breaches of confidentiality as well as discrimination. While this is in line with previous research from the UK [ 19 ], US [ 6 ], and from South Africa [ 34 ], our study has shown that many PLWH still experience enacted or anticipated stigma in the form of institutional or social dishonour. Although our study found that ‘courtesy’ stigma (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, 53.76% of pregnant women experienced HIVrelated stigmatization. The proportion was lower, comparative to 79.1% of internalized stigmatization in the United States, 77.8% of overt stigmatization in women from Chile, and 62.2% of anticipatory stigmatization in PLWH receiving ART in the Oromia region, Ethiopia (5,6,25); however, our number was found to be greater than the 29.0% of enacted stigmatization in PLWH in South Africa, and 25.2% in depressed pregnant women living with HIV in Kenya, and less than the 10% enacted stigmatization in participants at HIV clinics in Guangxi China (7,13,21). Difference in the HIV-related stigma was partially due to variations in social background and culture, participants' characteristics and perspectives toward HIV.…”
Section: Discussioncontrasting
confidence: 68%
“…HIV-related stigmatization is common, and it has been reported that 60-80% of HIV-infected adults have made at least one statement regarding HIV-related stigmatization (5,6). People living with HIV (PLWH) face internalized or overt stigmatization, such as being ashamed of HIV infection, being the subject of malignant gossip, and being discriminated against in their living settings (5)(6)(7)(8). Previous studies have shown that women have higher odds of experiencing both higher enacted stigmatization and internalized stigmatization than men at home and abroad (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…31,[36][37][38] Even though, magnitude of discrimination towards PLWHA is reduced in the last decade in Africa, it is still a public health problem which affects the successes of HIV-related programs in the continent. [39][40][41][42][43] In Ethiopia, the prevalence of HIV/AIDS-related discrimination is high. In Dessie (41.93%), 44 Jimma referral hospital (56%), 45 Oromia (62%), 24 Amhara (34%).…”
Section: Introductionmentioning
confidence: 99%